A framework for quantitative analysis of the causation of grounding accidents in arctic shipping. (October 2022) - Fu, Shanshan; Yu, Yuerong; Chen, Jihong; Xi, Yongtao; Zhang, Mingyang
Highlights: A framework is proposed for the quantitative causation analysis of grounding accidents in Arctic waters. Potential risk factors are identified for grounding accidents in Arctic shipping. The interdependency of the risk factors is reflected using the AcciMap model. The critical risk factors are identified for quantitative analysis using the BN model. RCOs are proposed for decreasing the risk of ship grounding in Arctic shipping. Abstract: The melting of Arctic Sea ice has significantly facilitated Arctic shipping. However, such increased shipping has brought about higher maritime accidents in Arctic waters, especially for grounding and fire/explosion accidents. The paper presents a framework for quantitative analysis of the causation of grounding accidents in Arctic shipping by developing an accident map (AcciMap) - Bayesian network (BN) model. First, the potential risk factors for grounding accidents in the Arctic shipping were identified according to 322 maritime accident investigation reports (MAIRs) - 299 global MAIRs of grounding accidents (including 5 in Arctic waters) and 23 MAIRs (except grounding accidents) in Arctic waters and related literature. Consequently, an AcciMap model is developed for describing the evolution of grounding accident scenarios and reflecting the interdependency of the identified risk factors. Then, a probabilistic model is proposed to evaluate the probability and severity of the grounding accident for presenting a convincing justification for risk control options (RCOs). The framework is applied for the quantitative analysis of a cruise ship grounding accident in Arctic waters. Results demonstrate (1) improved understanding of cruise ship grounding risk factors related to government supervision, shipping company management, technical and operational management, unsafe incidents and behaviors, and environmental conditions; (2) quantitative analysis of the evolution of grounding accident and better identification of the critical risk factors; (3) determination of RCOs for risk management in Arctic shipping.